An Appproach to Develop Teaching Model Using Design Thinking and Growth Mindset to Enhance Innovative Thinking Skills and Innovative Minds for Lower Secondary Students - Mungngam, Phattareeboon; Witchayawat, Wilaiphorn; Kongson, Rungtiwa; Punsrigate, Ketsaraphan (Journal of Graduate MCU KhonKaen Campus, 2024)
The objectives of this study were to: 1) examine the problem and manage the instructional that enhances innovative thinking skills and creativity of science teachers who are at the middle school level; and 2) study an approach to development of an instructional model using design thinking and growth mindset to enhance innovative thinking skills and innovative minds for lower secondary students. The target group consists of 7 science teachers. The research instruments include questions used in group discussions. The findings were as follows: 1) The current problems and needs in the management of science education concerning learners indicate that students are experiencing a decline in their learning ability; there are problems with scientific skills, a lack of basic knowledge, dependence on phones, a lack of commitment to study, a lack of motivation, an inadequacy of technological media, a lack of readiness for innovative media, and in the terms of teachers, a lack of expertise in using technological media. The commitment to develop innovative thinking skills and creative mindset involves using existing knowledge to create something new; furthermore, learning from basic data to build upon as innovation allows students to have a foundation related to the environment and to create diverse examples that integrate learning from the curriculum, use technology to create work and foster innovation, develop a habit of not copying others’ work, and contribute knowledge that encourages independent thinking based on one’s strengths and interests, leading to awareness and generating motivation. 2) The approach to development of an instructional model is as follows: Encourage students to think critically, ask questions by using various methods, promote out-of-the-box thinking, raise creativity, and present challenging problems, providing opportunities for them to design their own problem-solving methods. Setup the classroom environment that promotes independent thinking, provide examples of successful individuals and innovation to inspire, encourage teamwork, facilitate the exchange of ideas, and use supplementary activities. Developing and building on what exists in the local area, implementing community development projects that allow for practical training in creating prototypes or actual creative works, supporting students in showcasing their work, and listening to feedback.